Building brand meaning in social entrepreneurship organizations: the social impact brand model - Florian Lückenbach; Holger J. Schmidt; Jörg Henseler (Journal of Brand Management, 2022)
In the face of numerous complex challenges at the ecological, economic, and social levels, Social Entrepreneurship Organizations (SEOs) offer an approach that is both solution-oriented and future-oriented by combining profitability and purpose. However, the achievement of social goals is closely linked to the ability to operate successfully in competitive environments, in which differentiation strategies, in particular the creation of strong and authentic brands, are vital to survival. Although the new paradigm of brand management, the so-called co-creative paradigm, has been extensively researched in recent decades both in the for-profit and non-profit contexts, there is still scarce empirical research addressing the field of SEOs. To exploit the potential that the co-creation paradigm offers for SEOs, our paper introduces a social impact brand model (SIBM), which sheds new light on the design process of social entrepreneurial brand meaning. The findings identify key drivers in creating SEO brands by focusing on a dual-brand core that consists of an impact mission orientation and an entrepreneurial orientation, internal branding activities, the founder's personal brand, and relevant brand (co-)creators. By aligning their brand management activities with the SIBM, SEOs can create brands that have authentic and stable brand meanings while managing stakeholder groups' various expectations.
Keywords: 330; Social entrepreneurship organizations; Brand management; Brand co-creation; Social branding; Social entrepreneurial brand meaning